Review of the correlation between blood flow velocity and polycythemia in the fetus, neonate and adult: appropriate diagnostic levels need to be determined for twin anemia–polycythemia sequence. (2nd February 2016) - Lucewicz, A.; Fisher, K.; Henry, A.; Welsh, A. W.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2016; 47: 142–142 ABSTRACT: Twin anemia–polycythemia sequence (TAPS) is recognized increasingly antenatally by the demonstration of an anemic twin and a polycythemic cotwin using the middle cerebral artery peak systolic velocity (MCA‐PSV). While the MCA‐PSV has been shown to correlate well with anemia in singleton fetuses, the evidence to support its use to diagnose fetal polycythemia appears to be less clear‐cut. We aimed to evaluate fetal, neonatal and adult literature used to support the use of MCA‐PSV for the diagnosis of polycythemia. Comprehensive literature searches were performed for ultrasound evidence of polycythemia in the human fetus, neonate and adult using key search terms. Only manuscripts in the English language with an abstract were considered for the review, performed in June 2014. Fifteen manuscripts were found for the human fetus, including 38 cases of TAPS. Nine of these defined fetal polycythemia as MCA‐PSV < 0.8 multiples of the median (MoM), five used < 1.0 MoM and one used 0.8–1.0 MoM. Only two studies, involving a total of 15 cases, proposed a diagnostic level, acknowledging false‐positive and ‐negative cases, though neither reported sensitivities or specificities. Six neonatal studies (96 neonates) demonstrated evidence of decreased cerebral velocities in polycythemia and a consequent increase with hemodilution. In the adult, five studies (57 polycythemic adults) demonstrated increased flow or velocity with hemodilution. Neither neonatal nor adult studies conclusively defined levels for screening for polycythemia. Despite widespread adoption of a cut‐off of < 0.8 MoM in the published literature for the polycythemic fetus in TAPS, this is based upon minimal evidence, with unknown sensitivity and specificity. We recommend caution in excluding TAPS based purely upon the absence of a reduced MCA‐PSV. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.